Synthesis of Sorghum Starch–PVA/Gelatin Bioplastics Reinforced with Sorghum Stem Cellulose Nanofibers via Blend Ratio Tailoring - Darni, Yuli; lismeri, lia; Ginting, simparmin br; Setiawan, Aris (Reaktor, 2025)
This study aims to synthesis of sorghum starch–PVA/gelatin bioplastics reinforced with sorghum stem cellulose nanofibers through blend ratio tailoring in order to obtain bioplastics with properties comparable to LDPE. The mass ratios of sorghum starch to PVA/gelatin are varied at 9:1 and 8:2 (g/g), with a composition of 70% sorghum starch and 30% PVA. The nanofiber filler variations are 0 g, 0.1 g, and 0.2 g. Both starch and gelatin are sieved to 200 mesh. In the bioplastic fabrication process, glycerol concentration is set at 10% (w/w), with a stirring time of 35 minutes, gelatinization temperature of 95 °C, and stirring speed of 375 rpm. The analyses include tensile strength testing, elongation testing, functional group analysis using FTIR, morphological observation with SEM and TEM, and structural characterization with XRD. The best performance is achieved at a sorghum starch-PVA:gelatin mass ratio of 8:2 (g/g) with 0.2 g of nanofiber filler. The resulting bioplastic exhibits a tensile strength of 13.91 MPa, elongation of 3.00%, Young’s modulus of 4.63 MPa, water absorption of 1.8%, and density of 0.52 g/ml.